2019
DOI: 10.22159/ijpps.2019v11i6.28328
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Liquisolid Compacts of Lornoxicam

Abstract: Objective: Objective of the present investigation was to enhance the solubility and dissolution rate of poorly water-soluble drug lornoxicam using liquisolid technique with comparative determination of in vitro release profile of liquisolid compacts and conventional formulation of lornoxicam. Methods: Formulation was prepared by a liquisolid technique using different drug concentration in a liquid vehicle and different carrier/coating ratio. Prepared liquisolid compact was evaluated for Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When, sonication time increase from 30 to 90 second, then PDI was 0.309, 0.189 and 0.487, respectively for different NLCs formulations. It was observed that on 90 second of sonication time the PDI was increased and it was due to the high mechanical forced of sonication waves which were resultant in heat generation which leads to agglomerates or denaturing the lipid molecules after breaking the particles [19][20][21][22]. Value represent as mean±SD (n=6)…”
Section: Resultsmentioning
confidence: 99%
“…When, sonication time increase from 30 to 90 second, then PDI was 0.309, 0.189 and 0.487, respectively for different NLCs formulations. It was observed that on 90 second of sonication time the PDI was increased and it was due to the high mechanical forced of sonication waves which were resultant in heat generation which leads to agglomerates or denaturing the lipid molecules after breaking the particles [19][20][21][22]. Value represent as mean±SD (n=6)…”
Section: Resultsmentioning
confidence: 99%
“…About 5 ml of eluted sample was withdrawn at specified time intervals, filtered, and replaced with an equivalent amount of buffer into the vessel. The samples were suitably diluted and analyzed for Palbociclib using UV method spectrophotometrically at 220 nm [14].…”
Section: In Vitro Drug Dissolution Of Palbociclib Ssd'smentioning
confidence: 99%
“…Consequently, a dry, free-flowing, and compressible powder is obtained [6]. This technology is initially used in the purpose of improving drug solubility of poorly water-soluble drugs by using water-soluble polymer [7][8][9]. However, this method has been developed and the same principle was utilised to prepare sustained release formulation using hydrophobic polymers [5,10].…”
Section: Introductionmentioning
confidence: 99%